Case Report: A rare case of young adult progressive familial intrahepatic cholestasis-type 3 with a novel heterozygous pathogenic variant of ABCB4 - Zhu, Hao; Wang, Shengnan; Li, Li; Geng, Wenqian; Wan, Xiaoqiang; Hua, Rui; Wang, Dong; Gao, Pujun (Frontiers in Pediatrics, 2022)
Progressive familial intrahepatic cholestasis type 3 (PFIC-3) is a rare autosomal recessive disorder with poor prognosis. It is caused by pathogenic variants of the ATP binding cassette subfamily B member 4 (ABCB4) gene and usually progresses from chronic cholestasis with or without jaundice to portal hypertension and end-stage liver disease within the first to second decade of life. Few reported PFIC-3 patients presented with atypical clinical symptoms, therefore, often misdiagnosed if without family history. Herein, we report a 16-year-old male who was admitted to our hospital due to acute episodes of jaundice and intense pruritus, subsequently progressed to end-stage liver disease. Laboratory examinations showed no evidence of liver injury caused by viral, autoimmune, drug or liver tumors. Ursodeoxycholic acid and dexamethasone did not relieve his symptoms and he underwent liver transplantation successfully. Targeted next-generation sequencing identified that the patient was a compound heterozygote for two missense mutations (c.959C>T/c.1429C>A) in the ABCB4 gene. The mutation c.1429C>A (p.Q477K) is a novel heterozygous mutation. We constructed a three-dimensional model of this novel pathogenic variant using the SWISS MODEL program and found that the patient’s ABCB4 protein is an ATP hydrolysis deficient mutant. The postoperative pathological diagnosis showed intrahepatic cholestasis with progression to cirrhosis. Negative liver tissue immunohistochemistry of MDR3 was found in the explanted liver. The patient was diagnosed with PFIC-3, and his symptoms improved dramatically with liver transplantation. In conclusion, for young patients with acute cholestasis, pruritus, jaundice, growth retardation, and enlargement of the liver and spleen, the possibility of inherited metabolic liver diseases should be considered, detailed medical and family history should be collected, and metabolic screening tests as well as gene tests are necessary for correct diagnosis. Increasing the coverage of PFIC3 is meaningful and thus can improve the current understanding of this disease.